MOTOR ALALIYALÍ BALALARDÍŃ PSIXOMOTOR ÓZGESHELIKLERI HÁM OLARDÍŃ SOYLEWINDEGI NUQSANLARÍ - Ajimova, Z.G. (SCIENCE and SOCIETY, 2024)
The article talks about differences in the development of psixomovements and fine motor skills of the hands with alalia and speech disorders, and ways to eliminate deficiencies with the help of speech therapy - corrective exercises.
Keywords: alalia; motor alaia; psychological processes; perception; phonemic awareness; motor skills; fine motor skills